The New Encyclopedia of Science, 3 : Chemistry in Action - Morgan, Nina ohn and Clark, Owen Edward (New York Oxford University Press, 2003)
A color-illustrated encyclopedia of "chemistry in action" containing short definitions to approximately four hundred terms, cross-referenced to more than forty thematic spreads. Also includes knowledge maps and a time line.
Keywords: Chemistry -- Manufacturing processes -- Thermochemistry